Disaster Mitigation Model for Sustainable Tourism Development at the Nam Salu Openpit Geosite: Insights from the Belitong UNESCO Global Geopark - Idwan Fikri; Nana Sulaksana; Emma Rochima (International Journal of Science and Society, 2023)
This research aims to develop an effective disaster mitigation model to support sustainable tourism development at the Nam Salu Openpit Geosite, which is an integral part of the Belitong UNESCO Global Geopark. The qualitative approach method uses descriptive methods through case studies, namely the Open Pit Nam Salu (OPNS) geosite. The results of research conducted regarding the Open Pit Nam Salu (OPNS) Geosite in East Belitung revealed that the potential threat of disaster to this tourist site is very significant. The main factors influencing the vulnerability of OPNS Geosites to natural disasters include ecosystem damage due to unmanaged mining activities, changes in the landscape caused by intensive mining practices, and disruption of slope stability due to excessive exploitation of natural resources. In addition, climate change can also worsen the risk of disasters, including landslides and coastal erosion. Therefore, it is necessary to carry out structured disaster mitigation measures, including an early warning system, emergency management training, regular risk mapping, evacuation planning, development of a disaster information center, as well as education and public awareness programs to maintain the sustainability of the OPNS Geosite as a safe tourist destination. and sustainable.